THU0101 TORQUE TENO VIRAL LOAD FOR MONITORING OF BIOLOGICAL THERAPIES IN RHEUMATOID ARTHRITIS. (June 2019) - Studenic, Paul; Bond, Gregor; Kerschbaumer, Andreas; Becede, Manuel; Pavelka, Karel; Karateev, Dmitry; Stieger, Jutta; Puchner, Rudolf; Muller, Rudiger; Puchhammer-Stöckl, Elisabeth; Durechova, Martina; Loiskandl, Michaela; et al.
Abstract : Background: The apathogenic and highly prevalent Torque Teno Virus (TTV) is associated with the immunocompetence of its host and has been proposed for immunologic monitoring in solid organ transplantation. Objectives: Herein we explore TTV levels in rheumatoid arthritis (RA) patients receiving biological disease-modifying anti-rheumatic drugs (bDMARDs) in the context of clinical response. Methods: The BIOBIO study was designed to evaluate biomarkers for prediction of clinical response in patients with RA. Within this multicentre open-label trial, patients with insufficient response to MTX were randomized to TNFi (infliximab; INF), anti-IL-6 receptor (tocilizumab; TCZ), CTLA4-Ig (abatacept; ABA) or anti-CD20 (rituximab; RTX) in addition to MTX. TTV in peripheral blood samples was quantified at baseline and 3 months by RT-PCR. Results: TTV was measured in 95 RA patients [INF (n=23), TCZ (n=22), ABA (n=27) or RTX (n=23)]. Median TTV levels at baseline were 4.2x10 4 c/ml with no difference between the treatment groups. After 3 months of treatment patients with INF (p=0.018), ABA (p=0.071) and RTX (p≤0.001) showed an increase in TTV levels compared to baseline. There was no change in TTV in patients with TCZ, who were omitted from further analyses. TTV at 3 months after treatment was higher in patients achieving a SDAI85 response at month 6 (p=0.019). Levels of above 5.6x10 5 c/ml at month 3 showed a 67% specificity and 81% sensitivity for a SDAI85 response at month 6, corresponding to a positive likelihood ratio of 2.6 (95% CI: 1.6-4.1). Patients in the top tertile of month 3 TTV (>7.8x10 5 c/ml) had lower SDAI, CDAI and DAS28 and higher SDAI85 response rates at month 6 (OR: 4.18, CI: 1.41-16.42; p=0.012). The highest non-response rates were found in patients within the lowest TTV tertile (Table A ), and the highest remission rates were found in the highest TTV tertile (Table B ). No patient below a TTV value of 2.7x10 4 c/ml at month 3 showed SDAI85 treatment response at month 6. Conclusion: Our data suggest that TTV levels in patients with RA treated with INF, ABA or RTX at month 3 are associated with clinical responses at month 6, and thus may constitute a biomarker for therapeutic monitoring. Acknowledgement: This study was supported by a grant of the Austrian Science Funds (FWF, grant-ID: KLI072) Disclosure of Interests: Paul Studenic: None declared, Gregor Bond: None declared, Andreas Kerschbaumer Speakers bureau: Bristol-Myers-Squibb, Celgene, Pfizer, Manuel Becede: None declared, Karel Pavelka: None declared, Dmitry Karateev: None declared, Jutta Stieger: None declared, Rudolf Puchner: None declared, Rudiger Muller: None declared, Elisabeth Puchhammer-Stöckl: None declared, Martina Durechova: None declared, Michaela Loiskandl: None declared, Thomas Perkmann: None declared, Marta Olejárova: None declared, Elena Luchikhina: None declared, Carl-Walter Steiner: None declared, Michael Bonelli: None declared, Josef S. Smolen Grant/research support from: AbbVie, Eli Lilly, Janssen, MSD, Pfizer Inc, Roche, Consultant for: AbbVie, Amgen, AstraZeneca, Astro, Celgene, Celtrion, Eli Lilly, GlaxoSmithKline, ILTOO, Janssen, Medimmune, MSD, Novartis-Sandoz, Pfizer Inc, Roche, Samsung, Sanofi, UCB, Speakers bureau: AbbVie, Amgen, AstraZeneca, Astro, Celgene, Celtrion, Eli Lilly, GlaxoSmithKline, ILTOO, Janssen, Medimmune, MSD, Novartis-Sandoz, Pfizer Inc, Roche, Samsung, Sanofi, UCB, Daniel Aletaha Grant/research support from: AbbVie, Bristol-Myers Squibb, and MSD, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Medac, Merck, MSD, Pfizer Inc, Roche, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Medac, Merck, MSD, Pfizer Inc, Roche, and UCB